Professor Tadeusz Poklewski-Koziełł and the Research on the Development of the Agriculture Technology in Medieval and Modern Poland - Jerzy Maik (Fasciculi Archaeologiae Historicae, 2016)
One of the specializations at the Łódź Center of the Institute of Archaeology and Ethnology PAS is research on agricultural techniques in Middle Ages and in modern times. The research was initiated in the sixties of the 20th c. by Professor Tadeusz Poklewski by excavations in the region of Spicymierz, in central Poland. During the excavations he discovered traces of plowing with a moldboard plow dated to the 8th-10th c. Furthermore, on the basis of pottery scattering, he demarcated fields measuring around 5 ha each. The pottery found its way to the fields together with the compost, with which the fields were fertilized. It helped to determine the chronology of 7 fields to the 10th-12th c. and of 8 other ones to the 12th -14th c. In later years Professor did not lead any excavations of his own, which would relate to research on the history of agriculture, but he showed interest in such excavations, helped interpreting them. The archaeological material was analyzed under his guidance. On the route of the future highway, in Piaski-Nowa Wieś near Łowicz, Piotr Strzyż discovered 5 ditches, all parallel to each other. It was Professor Poklewski, who pointed to their similarity with the discoveries of Władysław Filipowiak in Dobropole, Pomerania, and helped this way to interpret them as traces of plowing with a one-sided moldboard plow. Also on the route of another future highway, in Pomorzany near Kutno, the expedition of the Łódź Center examined the remains of a grange, which functioned there from the 14th c., geared towards animal husbandry. In the beginning of the 19th c. the grange was relocated and in its place arable fields were established. The analysis of grange excavations was prepared and published under the editorship of Professor T. Poklewski. Research on agricultural techniques carried out by Professor T. Poklewski at the Łódź Center of IAE PAS allow to learn and understand not only the development of technology, the discoveries and inventions, but also the work of an ordinary man – the producer